2019
DOI: 10.1016/j.pnmrs.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance thermometry and its biological applications – Physical principles and practical considerations

Abstract: Most parameters that influence the magnetic resonance imaging (MRI) signal experience a temperature dependence. The fact that MRI can be used for non-invasive measurements of temperature and temperature change deep inside the human body has been known for over 30 years. Today, MR temperature imaging is widely used to monitor and evaluate thermal therapies such as radio frequency, microwave, laser, and focused ultrasound therapy. In this paper we cover the physical principles underlying the biological applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
120
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(120 citation statements)
references
References 244 publications
(434 reference statements)
0
120
0
Order By: Relevance
“…However, visualization of the intraprocedural ablated volume remains a large problem in focused ultrasound therapy. Thermal dose maps from MR thermometry are used during the treatment to visualize the treated volume, but fail to reliably predict the extent of ablation [10][11][12][13]. Post-treatment contrast enhanced MR imaging allows assessment of the nonperfused volume (NPV), the gold standard assessment of the degree of tumor ablation.…”
Section: Introductionmentioning
confidence: 99%
“…However, visualization of the intraprocedural ablated volume remains a large problem in focused ultrasound therapy. Thermal dose maps from MR thermometry are used during the treatment to visualize the treated volume, but fail to reliably predict the extent of ablation [10][11][12][13]. Post-treatment contrast enhanced MR imaging allows assessment of the nonperfused volume (NPV), the gold standard assessment of the degree of tumor ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the volume of magnetic susceptibility changes linearly with temperature 52 , and its effect on the 1 H resonance frequency shift is roughly an order of magnitude smaller than the electrical shielding effect 18 , 52 , 53 . As a result, calibration of the absolute thermometry method on the sample includes the sample-specific magnetic susceptibility shielding information for both sodium and proton.…”
Section: Discussionmentioning
confidence: 99%
“…Several different approaches for noninvasive thermometry, like impedance tomography, active and passive microwave imaging, CT, laser, infrared, ultrasound, MR-techniques, have been investigated in the last decades. Among all these different techniques, MR thermometry (MRT) has been elaborated most extensively and validated in clinical and experimental settings [20,21]. In addition, the gantry of the current MRI systems provides the possibility for mechanical integration with hyperthermia applicators [22].…”
Section: Introductionmentioning
confidence: 99%